Inadequate management of pregnancy‐associated listeriosis: lessons from four case reports. (5th July 2013) - Charlier, C.; Goffinet, F.; Azria, E.; Leclercq, A.; Lecuit, M.; Greub, G.
Abstract Listeria monocytogenes infection during pregnancy can lead to dramatic fetal or neonatal outcomes. No clinical trial has evaluated treatment options, and retrospective studies of cases are therefore important to define optimal regimens. We report four cases of materno–neonatal listeriosis illustrating inadequate antimicrobial therapy management and discuss recommended treatment options.